1987
DOI: 10.1007/bf02396620
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculitis in congenital rubella: ultrasound demonstration

Abstract: A female infant with proven congenital rubella infection was referred for cranial ultrasound examination. Intraventricular strands and debris with periventricular echogenic foci were demonstrated. These findings, typical of ventriculitis, have not previously been reported in congenital rubella. Mental retardation is the rule in symptomatic cases and therefore early recognition of central nervous system involvement is of benefit in assessing the long-term neurodevelopmental outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Thirty-one patients with CRS were included. [18][19][20][21][22][23][24][25][26][27][28] The average gestational weeks and birth weights were 37.8 ± 2.0 weeks and 2237.5 ± 481.6 g, respectively. The radiological evaluation was performed at 10.9 ± 14.7 months of age.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one patients with CRS were included. [18][19][20][21][22][23][24][25][26][27][28] The average gestational weeks and birth weights were 37.8 ± 2.0 weeks and 2237.5 ± 481.6 g, respectively. The radiological evaluation was performed at 10.9 ± 14.7 months of age.…”
Section: Resultsmentioning
confidence: 99%
“…Computed tomography (CT) scan findings feature basal ganglia calcifications. 20,21 MRI findings include periventricular leukomalacia, delayed myelination, and hydrocephalus. 22 A case series in 1991 suggested that severity of MRI abnormalities may correlate with functional status and may be prognostic in the postnatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocephalus has been reported after congenital toxoplasmosis and cytomegalovirus [13,14]. Though ventriculomegaly and ventriculitis have been infrequently reported before in association with CRS, communicating hydrocephalus is not a common complication of congenital rubella infection and has never been previously reported [15,16].…”
Section: Discussionmentioning
confidence: 99%